If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + -10) * 3x = 0 Reorder the terms: (-10 + 9x) * 3x = 0 Reorder the terms for easier multiplication: 3x(-10 + 9x) = 0 (-10 * 3x + 9x * 3x) = 0 (-30x + 27x2) = 0 Solving -30x + 27x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x(-10 + 9x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-10 + 9x)' equal to zero and attempt to solve: Simplifying -10 + 9x = 0 Solving -10 + 9x = 0 Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 9x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 9x = 0 + 10 9x = 0 + 10 Combine like terms: 0 + 10 = 10 9x = 10 Divide each side by '9'. x = 1.111111111 Simplifying x = 1.111111111Solution
x = {0, 1.111111111}
| -2x+9=2x-7 | | -6-m-8=24 | | .333x=-9 | | 3.2v-5.5=3.4v+1.1 | | 3(3y-7)+y-8= | | 9x+9=92 | | -8(6x-2)=-7(8+6x) | | -r+6r-5(6r-4)= | | X-29=10 | | 6+4(m+13)-9m= | | -2r+6(r-1)+3r-(4-r)=-(r+5)-5 | | -1+4x+6x-20= | | (3x^2y^3)(4x^5y)= | | x^2+2cx-1=0 | | 3x-15+4x=5x-27 | | 8c-12-5c+4= | | 10a=18a | | 5-2(3a-4)-(4+a)-1= | | 24=6y | | 5-3a+4=a-7 | | (2b+8)17= | | -x+6y=12 | | 1-6x-1=6(1-8x)-10(3-5x) | | x^3+8x^2-9x-72=0 | | 3x+x-28=124 | | x^3+8x^2-9x+72=0 | | 15+4z=32z^2 | | 3x^2+4x-10=8 | | -10(1+8x)+6=3x-4 | | -2+2x=8 | | 2(-6-12)=-2c-12 | | 25y^2=121 |